The European species of Chalarus Walker, 1834 revisited (Diptera: Pipunculidae) - Kehlmaier, Christian; Assmann, Thorsten (Zootaxa, 2008)
The European representatives of the pipunculid genus Chalarus are taxonomically revised. Chalarus absconditus Kehlmaier spec. nov., C. immanis Kehlmaier spec. nov., C. marki Kehlmaier spec. nov. and C. saxonicus Kehlmaier spec. nov. are described as new to science. Males of C. pughi Coe, 1966, C. clarus Jervis, 1992 and C. longicaudis Jervis, 1992 are characterized for the first time, as is the female for C. griseus Coe, 1966. A lectotype is designated for Chalarus velutinus Macquart, 1834 and the name is proposed for synonymy with C. spurius (Fallén, 1816). Chalarus parmenteri Coe, 1966 and C. perplexus Jervis, 1992 are proposed as junior synonyms of C. holosericeus (Meigen, 1824). The assignment of males and females is established through DNA barcodes, using fragments of the mitochondrial coding gene cytochrome oxidase subunit I (coxI) and nuclear Second Internal Transcribed Spacer region (ITS2). An identification key to the European representatives of the genus is provided, including figures of male and female terminalia for most species.